TAAR1 induces a disturbed GSK3β phosphorylation in recurrent miscarriages through the ODC. Issue 2 (February 2018) - Stavrou, Stavroula; Gratz, Michael; Tremmel, Eileen; Kuhn, Christina; Hofmann, Simone; Heidegger, Helene; Peryanova, Mina; Hermelink, Kerstin; Hutter, Stefan; Toth, Bettina; Mayr, Doris; Mahner, Sven; et al.
Abstract : Objectives: Thyroid hormones play an important role in the maintenance of pregnancy. Their derivates, endogenous amines, act via binding to the trace amine-associated receptor (TAAR1). The aim of our study was to analyse the regulation of TAAR1, serine/threonine kinase (pGSK3β) and ornithine decarboxylase (ODC) in placentas of healthy pregnancies, spontaneous (SM) and recurrent miscarriages (RM) and to investigate the influence of thyroid hormone derivates on TAAR1 expression in trophoblast model cells in vitro . Methods: Patients with SM ( n  = 15) and RM ( n  = 15) were compared with patients with healthy pregnancies ( n  = 15) (pregnancy weeks 7–13 each). Immunohistochemistry was applied to analyse placental TAAR1, pGSK3β and ODC expression. Protein expression of the receptors after stimulation with T3, T1 AM and RO5203548 in BeWo trophoblast model cells was determined via Western blot. Double-immunofluorescence was used to determine placental expression of TAAR1 and ODC. Results: Levels of TAAR1, pGSK3β and ODC were higher in placentas of RM in comparison to healthy controls. Stimulation of BeWo cells with T3, T1 AM and RO5203548 significantly increased TAAR1 expression. ODC expression in BeWo cells was upregulated through T3 . Via double-immunofluorescence, TAAR1 and ODC-positive EVT could be detected. Conclusions: Upregulation of placental TAAR1 may indicate an increased decarboxylation of thyroid hormones in miscarriages. Patients with RM may have a lack of T3 through an enhanced transformation of T3 into T1 AM induced by the ODC. Future investigations could be carried out to analyse what role a prophylactic T3 substitution plays for patients.